PROTOTYPE SISTEM PENDAFTARAN RAWAT JALAN PADA RSUD LARANTUKA NUSA TENGGARA TIMUR BERBASIS MOBILE (INTI Nusa Mandiri, 2023)
Abstract—The role of the hospital is very helpful in efforts to improve the quality of public health, for this reason the need for fast and appropriate services so that human resources are maintained for their survival. At dr. Hospital Hendrikus Fernandez Larantuka East Nusa Tenggara, the registration service still uses the intranet system or local network and system errors often occur so that the patient registration process is hampered. In addition, the system created on the intranet network also has drawbacks, one of which is that it can only be accessed by people who are connected to the building's network. With these problems, there is a need for a mobile-based application that can be accessed directly by the public in real time from anywhere and any time. The purpose of this study is to create a mobile-based application design that is capable of processing inpatient registration services at hospitals with an attractive and user-friendly appearance. The method used in this study is the prototyping method. This method is a software development model by creating a prototype or model to provide an overview to the user by going through 5 stages, namely communications, quick plan, quick design model, prototype construct, and development delivery and feedback. The tool used in making this prototype is the Figma application. The results of this study are that there is an application prototype that can be used as reference material for RSUD dr. Hendrikus Fernandez Larantuka, East Nusa Tenggara, in developing his system so that the inpatient registration process can be carried out by the community anytime and anywhere. Likewise, information from the hospital can be received in real time by the public through the mobile-based hospital inpatient application.
Keywords: Patient Service; prototype; Information System